In vitro evaluation of Lactobacillus plantarum as direct-fed microbials in high-producing dairy cows diets - Monteiro, Hugo Fernando (2019)
The objectives of this study were: 1) to compare the effects of live yeast (LY), yeast fermentation product (YFP), a mix of Lactobacillus acidophilus and Propionibacterium freudenreichii (MLP), and Lactobacillus plantarum included as additives in dairy cows’ diets on in vitro ruminal fermentation and gas production (GP); and 2) to evaluate the effects of L. plantarum as direct-fed microbials (DFM) in dairy cows’ diets on in vitro ruminal fermentation, GP, nutrient digestibility, and N metabolism. Three experiments were carried out: Exp. 1 had the objective to compare all additives regarding ruminal fermentation parameters: an Ankom GP system was used in a completely randomized design, consisting of four 48 h incubations, and eight replications per treatment. There were eight treatments: a basal diet without additive (CTRL) or with one of the following additives: LY, YFP, MLP, or L. plantarum at four levels (% of diet Dry Matter (DM)): 0.05% (L1), 0.10% (L2), 0.15% (L3), and 0.20% (L4). In Exp. 2, a batch culture was used to evaluate ruminal fermentation, and CO2 and CH4 production using the same treatments and a similar experimental design, except for having 16 replications per treatment. Based on Exp. 1 and 2 results, Exp. 3 aimed at evaluating the effects of the L. plantarum on ruminal true nutrient digestibility and N utilization in order to evaluate the use of L. plantarum as DFM. The treatments CTRL, MLP, L1, and L2 were used in a replicated 4 × 4 Latin square design using a dual-flow continuous culture system. Data were analyzed using linear and nonlinear regression; treatment means were compared through contrasts, and L treatments in Exp. 1 and 2 were tested for linear, quadratic, and cubic effects. In Exp. 1, all treatments containing additives tended to reduce OM digestibility as well as reduced total volatile fatty acids (VFA) concentration and total GP. The YFP had greater OM digestibility than LY, and MLP treatment had greater total VFA concentration compared to L. plantarum treatments. In Exp. 2, additives reduced CO2 production, and there were no major differences in CH4. In Exp. 3, all additives reduced NH3 -N concentration. In conclusion, pH and lactate concentration were not affected in all three experiments regardless of additive tested, suggesting that these additives may not improve ruminal fermentation by pH modulation; and L. plantarum may improve ruminal N metabolism when used as DFM in high-producing dairy cows’ diets, mainly by reducing NH3 -N concentration.